CHATBOT DESIGN BASED ON RULES TO SUPPORT MEDICAL INFORMATION SERVICE AT PT. REKSA NUSINDO SEJAHTERA - Arianto, Habib; Panjaitan, Dodi Syahputra; Ayuningsih, Ekatri; Rahma, Maulidya (Bahasa Indonesia, 2023)
PT Reksa Nusindo Sejahtera is a medical appliances company that sells health and medical devices for personal and public use. PT Rekza Nusindo sells medical appliances by implementing web-based applications to enhance its own branding. However, the provision of information on the website pages is often a question for its consumers so it seems that web-based applications are still less interactive in serving consumers within 24 hours. The AI chatbot will be implemented to support the information service at the PT Reksa Nusindo Sejahtera. PT Recsa Nusindos use the AI Chatbot service to make much more efficient, increase customer satisfaction and improve operational efficiency. The design of AI chatbots using the Watson Assistant Service will be deployed on the website of PT reksa nusindos to support information and respond to questions asked by consumers related to medical appliances quickly and accurately.